Sustained 52‐week efficacy and safety of triple therapy with dapagliflozin plus saxagliptin versus dual therapy with sitagliptin added to metformin in patients with uncontrolled type 2 diabetes - Handelsman, Yehuda (Diabetes Obes Metab, 2019)
AIMS: To compare the efficacy and safety of an intensification strategy of early triple combination therapy with dapagliflozin (DAPA) plus saxagliptin (SAXA) to a dual therapy strategy with sitagliptin (SITA) in patients with type 2 diabetes who are inadequately controlled with metformin (MET) monotherapy. MATERIALS AND METHODS: This multinational, active‐controlled, parallel‐group phase 3b trial randomized 461 patients, at least 18 years of age, with glycated haemoglobin (HbA1c) of 8%–10.5% (64–91 mmol/mol), to either DAPA plus SAXA or SITA, added to MET, for a 26‐week double‐blind treatment period and an extension of a 26‐week blinded treatment period. RESULTS: Mean (± SD) baseline HbA1c was 8.8% ± 0.9% (73.0 ± 9.3 mmol/mol). DAPA plus SAXA (n = 232) provided a greater reduction from baseline in HbA1c at Weeks 26 and 52 compared with SITA (n = 229) (adjusted mean ± SE change, Week 26: −1.41 ± 0.07% vs −1.07 ± 0.07% [−15.4 ± 0.8 mmol/mol vs 11.7 ± 0.8 mmol/mol]; P = 0.0008; Week 52: −1.29 ± 0.08% vs −0.81 ± 0.09% [14.1 ± 0.9 mmol/mol vs 8.9 ± 1.0 mmol/mol]). The between‐group difference in adjusted mean (95% CI) change from baseline in HbA1c increased from −0.34 (−0.54, −0.14) at Week 26 to −0.48 (−0.71, −0.25) at Week 52. DAPA plus SAXA was generally well tolerated and the incidence of adverse events was similar in both treatment arms. CONCLUSIONS: Early intensification to triple therapy with DAPA plus SAXA results in better, more durable glycaemic control than addition of SITA only (dual therapy) in patients with high HbA1c levels who are uncontrolled with MET monotherapy.